The civilization of the Renaissance in Italy : - Burckhardt, Jacob
For nineteenth-century Swiss historian Jacob Burckhardt, the Italian Renaissance was nothing less than the beginning of the modern world - a world in which flourishing individualism and the competition for fame radically transformed science, the arts, and politics. In this landmark work he depicts the Italian city-states of Florence, Venice and Rome as providing the seeds of a new form of society, and traces the rise of the creative individual, from Dante to Michelangelo. A fascinating description of an era of cultural transition, this nineteenth-century masterpiece was to become the most influential interpretation of the Italian Renaissance, and anticipated ideas such as Nietzsche's concept of the 'Ubermensch' in its portrayal of an age of genius.